Analisis Kemampuan Pemecahan Masalah Matematis Siswa Berdasarkan Self Confidence Melalui PBL dengan Pendekatan PMR - Maria Dea Pramudita; Lukita Ambarwati; Flavia Aurelia Hidajat (SAP (Susunan Artikel Pendidikan), 2026)
This study aims to describe students' mathematical problem-solving abilities based on their self-confidence levels through Problem Based Learning (PBL) with a Realistic Mathematics Learning (RMAT) approach. This study used a descriptive qualitative approach with nine tenth-grade students selected purposively based on the results of a self-confidence questionnaire, problem-solving ability test results, observations, and interviews. The results showed that students with high self-confidence tended to be able to solve problems completely and systematically according to Polya's steps. Students with moderate self-confidence showed quite good abilities, but were not consistent in re-checking their answers. Meanwhile, students with low self-confidence experienced difficulties from understanding the problem to solving it. The PBL learning process with the RMAT approach was proven to help students relate mathematical concepts to real contexts, build self-confidence, and increase active involvement in the problem-solving process.